4G/5G antenna with small clearance for metal frame smartphone applications. Issue 2 (16th September 2020) - Jin, Guiping; Wang, Wei; Sun, Yi; Lu, Dujiao; Liao, Shaowei
Abstract: An 4G/5G antenna with small clearance for metal frame smartphone applications is proposed. The proposed antenna consists of metal frame, inverted‐T feeding lines, S‐shaped branch, and the system ground on which U‐shaped slot is etched. The metal frame is broken and there is a 2 mm open slit on the metal frame. There is a 2 mm gap between the metal frame and the substrate. The ground clearance of the proposed antenna is 34.5 × 5.5 mm. Inverted‐T feeding lines are connected to the metal rim. Using the multiple radiation patterns of S‐shaped branches and the coupling ring mode of S‐shaped branch and ground‐extending metal frames, the measured −6 dB impedance bandwidth are 1680 to 2820 MHz and 2870 to 5500 MHz bands, which can fully cover DCS1800, PCS1900, UMTS2100, LTE2400, 2600 (1710 to 2690 MHz), and 5G N77/N78/N79 (3300‐4200 MHz, 4400‐5000 MHz) bands. The measured efficiency is greater than 43% in desired bands. The proposed antenna has the advantages of small ground clearance, wide bandwidth, and no lumped elements.